2006
DOI: 10.1145/1188816.1188821
|View full text |Cite
|
Sign up to set email alerts
|

Transparent adaptation of single-user applications for multi-user real-time collaboration

Abstract: Single-user interactive computer applications are pervasive in our daily lives and work. Leveraging single-user applications for supporting multi-user collaboration has the potential to significantly increase the availability and improve the usability of collaborative applications. In this article, we report an innovative Transparent Adaptation (TA) approach and associated supporting techniques that can be used to convert existing and new single-user applications into collaborative ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
130
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 13 publications
0
130
0
Order By: Relevance
“…The seminal work of Sun et al [19] proposes the transparent adaptation (TA) approach to convert single-user applications into collaborative multi-user applications. The cornerstone of TA is operational transformation (OT) [4].…”
Section: Related Workmentioning
confidence: 99%
“…The seminal work of Sun et al [19] proposes the transparent adaptation (TA) approach to convert single-user applications into collaborative multi-user applications. The cornerstone of TA is operational transformation (OT) [4].…”
Section: Related Workmentioning
confidence: 99%
“…It is known that collaborative editors manipulate share objects that admit a linear structure [3,13,15]. This structure can be modelled by the list abstract data type.…”
Section: Shared Data Objectmentioning
confidence: 99%
“…For instance, an element may be regarded as a character, a paragraph, a page, an XML node, etc. In [15], it has been shown that this linear structure can be easily extended to a range of multimedia documents, such as MicroSoft Word c and PowerPoint c documents. It is clear that combinations of these operations enable us to define more complex ones, such as cut/copy and paste, that are intensively used in professional text editors.…”
Section: Shared Data Objectmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique consists of an algorithm which transforms an update (previously executed by some other user) according to local concurrent updates in order to achieve convergence. It is used in many collaborative editors including Joint Emacs [8] (an Emacs collaborative editor), CoWord [13] (a collaborative version of Microsoft Word), CoPowerPoint [13] (a collaborative version of Microsoft PowerPoint) and, more recently, the Google Wave (a new google platform 3 ).…”
Section: Introductionmentioning
confidence: 99%